2014
DOI: 10.1016/j.jana.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Train-the-Trainer HIV Education: A Model From Vietnam

Abstract: As HIV prevention and treatment efforts expand around the globe, local capacity-building to update and maintain nurses' HIV competence is essential. The purpose of this project was to develop and sustain a national network of nurse-trainers who could provide ongoing HIV continuing education and training experiences to Vietnamese nurses. Over the course of 6 years, 87 nurses received training to become HIV trainers; their HIV knowledge increased significantly (p = .001), as did teaching self-confidence (p = .00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…Studies assessing training impact on other health-related aspects such as HIV or specific psychotherapies show similar results (Deren, Kang, Mino, & Guarino, 2012;Diesel, Nsagha, Sab, Taliaferro, & Rosenburg, 2011;Jaffray et al, 2014;Nyamathi et al, 2008;Williams et al, 2014;Wolfe et al, 2013). Gohns, Buetow, and McCormick (2002), reported that general practitioners, pharmacists and nurses trained together reported satisfaction and benefits from the training.…”
Section: Discussionmentioning
confidence: 83%
“…Studies assessing training impact on other health-related aspects such as HIV or specific psychotherapies show similar results (Deren, Kang, Mino, & Guarino, 2012;Diesel, Nsagha, Sab, Taliaferro, & Rosenburg, 2011;Jaffray et al, 2014;Nyamathi et al, 2008;Williams et al, 2014;Wolfe et al, 2013). Gohns, Buetow, and McCormick (2002), reported that general practitioners, pharmacists and nurses trained together reported satisfaction and benefits from the training.…”
Section: Discussionmentioning
confidence: 83%
“…In a study designed to develop and sustain a national level of nurse educators capable of training future nurses on HIV-related subjects in Vietnam [18], 87 nurse educators trained using the TTT model were able to each train an average of 770 healthcare workers over a 6 years period [18]. Similarly, in a study designed to improve the patient resuscitation skills of isolated doctors, 8 rural, non-hospitalist physicians trained 57 doctors within a 6- and 12-week follow-up period [19].…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] These programs range from large entities such as "Advanced Trauma Life Support" instructor courses for healthcare providers, 18 to health awareness courses offered to the U.S. public, 20 and to HIV-outreach programs in developing countries. 19 Instructor candidates indicated that the "IHISTrain the Trainer" course material significantly increased their level of awareness of firefighter-specific burn issues and confidence to teach the material to firefighters. Despite the fact that the average course participant had extensive experience in their individual job (15 years) and in burn care (12 years), they still found the course to be of benefit.…”
Section: Discussionmentioning
confidence: 99%